Factors Influencing People's Decision to Pay Zakat, Infaq and Sedekah (ZIS) in Baitul Mal Banda Aceh City - *Al Munawir; Sartiyah Sartiyah (Riwayat: Educational Journal of History and Humanities, 2022)
The aim of the research is to examine the influence of factors that determine people's decisions in giving zakat, infaq, and sedekah at amil zakat institution. Some influencing factors are level of publication, promotion, reputation, religiosity, and motivation to the community's decision to pay ZIS at Baitul Mal of Banda Aceh City. The method used in this research is quantitative by using primary data. The data collection was conducted by distributing questionnaires directly to the research object. Each variable was measured a Likert scale. The research population was the people of Banda Aceh City aged 15-64 years and above who have jobs and income. The sample selection technique used is convenience sampling, the research object consisted of 100 respondents. Data processing was carried out by using binary logistic regression analysis. The results of this study indicated that publication, promotion, reputation, religiosity, and motivation positively and significantly impacted the community's decision in paying ZIS at Baitul Mal of Banda Aceh City, either partially or simultaneously. The results also showed that the community did not only require an increase in a good understanding of ZIS and its benefits, but they also demanded the reputation of Baitul Mal institution to be improved in order to encourage them to pay ZIS at Baitul Mal of Banda Aceh City.